Hypoxia increases Annexin A2 expression in osteoblastic cells via VEGF and ERK - Genetos, Damian C. (Bone, 2010)
Vascular endothelial growth factor (VEGF) stimulated angiogenesis is critical for endochondral ossification that occurs during bone development, and bone repair. Under these circumstances, VEGF production appears to be driven by low oxygen tension, under the control of the hypoxia inducible factor-α family of transcription factors (HIF-α). Annexin 2 (AnxA2) a calcium dependant phospholipid binding protein has been implicated in VEGF-mediated retinal neovascularization and is upregulated by VEGF in choroid retinal endothelial cells. AnxA2 is also expressed in cells of the osteoblast lineage and chondrocytes and may play a role in matrix mineralization. In this paper we examined the effects of hypoxia (1% O(2)) and VEGF on the expression of AnxA2 in osteoblastic MC3T3-E1 cells. Hypoxia, desferrioxamine (hypoxia mimetic) and recombinant VEGF all increased AnxA2 mRNA and protein levels in osteoblastic cells. The hypoxia-induced increase in AnxA2 was inhibited by a blocking antibody to VEGF-R1, however, VEGF(120), a VEGF-R1 agonist demonstrated no influence upon Anxa2 expression. This suggests that VEGF induction of Annexin A2 is not mediated via VEGF-R1 agonism alone, but by VEGF-R1 and Neuropilin-1 or Neuropilin-2 heterodimers. Additionally we demonstrated that VEGF-stimulated changes in AnxA2 expression via a pathway involving Src and MEK kinase. These data demonstrate that AnxA2 expression in osteoblasts is under the control of VEGF, which may have implications for both angiogenesis and bone mineralization under low oxygen conditions.